2016
DOI: 10.1242/dev.128926
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis is required for axonal growth

Abstract: During early development, neurons undergo complex morphological rearrangements to assemble into neuronal circuits and propagate signals. Rapid growth requires a large quantity of building materials, efficient intracellular transport and also a considerable amount of energy. To produce this energy, the neuron should first generate new mitochondria because the pre-existing mitochondria are unlikely to provide a sufficient acceleration in ATP production. Here, we demonstrate that mitochondrial biogenesis and ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 38 publications
0
76
0
Order By: Relevance
“…, 2015), although we did not determine whether mitochondria were involved. However, other studies demonstrated the importance of mitochondria in axonal growth (Mattson and Partin, 1999; Vaarmann et al. , 2016).…”
Section: Resultsmentioning
confidence: 97%
“…, 2015), although we did not determine whether mitochondria were involved. However, other studies demonstrated the importance of mitochondria in axonal growth (Mattson and Partin, 1999; Vaarmann et al. , 2016).…”
Section: Resultsmentioning
confidence: 97%
“…It has been shown that PGC-1α regulates mitochondrial density in neurons (Wareski et al, 2009; Cheng et al, 2012; Vaarmann et al, 2016). To assess the involvement of PGC-1α in the increased mitochondrial generation and activity during dendritic development, we monitored PGC-1α expression in Purkinje cells of various developmental stages.…”
Section: Resultsmentioning
confidence: 99%
“…For example, synaptic activity-dependent Ca 2+ influx stimulates the rapid insertion of AMPA glutamate receptors into the postsynaptic membrane while also inducing the translation of mRNA encoding the protein Arc, which mediates endocytosis of AMPA receptors (Kindler and Kreienkamp, 2012). Via activation of kinases, synaptic Ca 2+ influx also activates transcription factors including cyclic AMP response element-binding protein (CREB) and PGC-1α (Cohen et al, 2015; Vaarmann et al, 2016), which then upregulate the expression of genes encoding various proteins involved in neuronal plasticity and cellular stress resistance (Mattson, 2012). Additional fine-tuning of subcellular Ca 2+ dynamics is conferred by Ca 2+ uptake and release mechanisms operative in the endoplasmic reticulum and mitochondria.…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…A picture is emerging in which pathways activated during the metabolic challenges of exercise and fasting prepare the cells to grow during the recovery period (rest, feeding, and sleep) (Mattson et al, 2018). In the case of neurons, such intermittent metabolic switching may stimulate mitochondrial biogenesis to enable neurite outgrowth and the formation of new synapses (Cheng et al, 2012; Vaarmann et al, 2016). In addition, recent findings suggest that intermittent metabolic switching enhances the function, stress resistance, and quality control of mitochondria, in part by inducing the expression of the mitochondrial protein deacetylase SIRT3.…”
Section: Metabolic Factors Can Accelerate or Decelerate Brain Agingmentioning
confidence: 99%